On the novel coronavirus (COVID-19): a global pandemic - Louis-Jean, James; Aime, Magdonald (Jurnal Teknologi Laboratorium, 2020)
Coronaviruses (COVS) are viruses transmitted through droplets of sputum from an infected person. Analyses identify COVS as zoonotic pathogens, possibly resulting from human-animal contact at animal markets. They share overlapping genetic characteristics with the avian influenza viruses from China. COVS released from humans through droplets of sputum and may land on various surfaces, which poses exposure risks; as studies have shown the virus can exist intact for a relatively long period of time (several days). The recent highly pathogenic COVS outbreak (COVID-19) emerged in Wuhan, China in 2019, include Severe Acute Respiratory Syndrome (SARS-COVS). This highly transmittable disease causes pneumonia and severe respiratory illnesses similar to SARS and MERS; it has a global mortality rate of about 6.13%. The virus has rapidly become a global pandemic, causing major global issues, including health, economic, and age-preference, among other issues. This text summarizes the nature of the emerging COVID-19 global pandemic while analyzing several factors concerning the etiology of the virus. This is done in an urgent effort to educate and provide relevant information about the virus.